Magellanic Woodpeckers in Three National Parks of Central-Southern Chile: Habitat Effects and Population Variation over the Last Two Decades [Le Pic de Magellan Dans Trois Parcs Nationaux Du Centre-Sud Du Chili: Effets de L Habitat Et Variation Des Populations Durant Les Deux Dernières Décennies] - Vergara-Egert, P; Fierro-Tapia, C (Resilience Alliance, 2017)
A major challenge for protected areas is providing wildlife with enough suitable habitat to cope with stochastic environment and increased pressure from the surrounding landscapes. In this study, we addressed changes in local populations of Magellanic Woodpeckers (Campephilus magellanicus) occupying three national parks of central-southern Chile. We compared the breeding and postbreeding abundance of woodpeckers during the 1990s with the present (2016) abundance (n = 4 years), and assessed the extent to which abundance was explained by forest type and quality of foraging habitat (as quantified through the plant senescence reflectance index; PSRI). Results show a distinctive temporal variation in woodpecker abundance at each park, with local populations of Magellanic Woodpeckers declining by 42.2% in Conguillío National Park, but increasing by 34.3% in Nahuelbuta National Park. Woodpeckers responded to forest conditions within each park such that their abundance increased with high quality of foraging habitat, i.e., large PSRI values, and the presence of old-growth Monkey puzzle (Araucaria araucana) - Nothofagus pumilio mixed forest. Anecdotal evidence suggests that populations of woodpeckers in Conguillío National Park might have responded negatively to large-scale disturbances from recent forest fires affecting part of the forest area within park. Because stochastic events seemed to strongly mediate population changes, our findings suggest that regional conservation of Magellanic Woodpeckers requires expanding the current conservation area network in central-southern Chile. © 2017 by the author(s).